A STUDY OF OUTCOME INDICATORS FOR PATIENTS’ SAFETY AND PROFESSIONAL NURSES’ SAFETY IN THE EMERGENCY DEPARTMENT OF TERTIARY HOSPITALS: A DELPHI METHOD - Yodbuddee, Ratthapol; Wisesrith, Wasinee (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
This study was descriptive research using the Delphi technique. The objective was to study outcome indicators for the safety of patients and professional nurses in the context of emergency departments in tertiary hospitals. The participants were 20 experts in the fields of emergency nursing and care for emergency department patients at tertiary hospitals. They were selected by purposive and snowball sampling. The instruments consisted of questionnaires and an interview form that were tested for content validity by qualified experts. Qualitative data were analyzed by content analysis and descriptive statistics such as median and interquartile ranges. The results found that the outcome indicators for patients’ safety in the emergency departments of tertiary hospitals consisted of the following 7 domains with 59 indicators: 1) Safety in receiving emergency care, 2) Safety in inter-hospital referral systems, 3) Safety of intra-hospital referral systems and continuity of care, 4) Safety in communication and relationships with health care teams, 5) Safety from infections, 6) Environmental system safety, and 7) Medication and blood safety (Md = 3.75 - 4.75, IR = .25 – 2.02). On the other hand, the outcome indicators for professional nurses’ safety in the emergency departments of tertiary hospitals consisted of the following 5 domains with 62 indicators: 1) Safety in the working environment and prevention of violence; 2) Safety from having infection prevention; 3) Safety from care in the referral system and legal implications; 4) Safety from receiving psychological care; and 5) Information safety (Md = 4.12 – 4.75, IR = .25 – 1.16). The results of this research can be used as an outcome evaluation guideline to improve the patient care process to be appropriate and efficient, in addition to guiding the development of work safety behaviors for professional nurses in emergency departments at the tertiary hospital level.